Causal relationships of neonatal jaundice, direct bilirubin and indirect bilirubin with autism spectrum disorder: A two-sample Mendelian randomization analysis - Chen, Li-wen; Zhang, Yi; Xu, Dou-dou; Wang, Yang; Gao, Hui (Frontiers in Public Health, 2023)
Background：Multiple systematic reviews and meta-analyses have examined the association between neonatal jaundice and ASD risk, but their results have been inconsistent. This may be because the included observational studies could not adjust for all potential confounders. Mendelian randomization study can overcome this drawback and explore the causal relationship between the both. Methods：We used the data of neonatal jaundice, direct bilirubin (DBIL), indirect bilirubin (IBIL) and ASD collected by genome-wide association study (GWAS) to evaluate the effects of neonatal jaundice, DBIL and IBIL on ASD by using a two-sample Mendelian randomized (MR) . The inverse variance-weighted method(IVW) was the main method of MR analysis in this study. Weighted median method, MR-Egger regression and mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) test were used to access sensitivity. Results：There was no evidence of an effect of neonatal jaundice (OR, 1.002, 95% CI, 0.977-1.027), DBIL (OR, 0.970, 95% CI, 0.884-1.064) and IBIL (OR, 1.074, 95% CI, 0.882-1.308) on ASD risk by IVW test. In the weighted median method, MR-Egger regression and leave-one-out analysis, the results were robust and and no heterogeneity or pleiotropy was observed. Conclusions：We found that neonatal jaundice, DBIL and IBIL were not associated with ASD in this study. However, this paper did not explore the effect of severity and duration of jaundice on ASD in different ethnic populations, which may require further research.